On the existence of Nash equilibrium in a non-cooperative, n-person, linear differential games with measures as coefficients - Malafyeev, Oleg A.; Wyderka, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the existence of [epsilon]-equilibrium in the sense of Nash for linear differential games with measures as coefficients and with fixed time duration is studied. The strategies of the players are understood in a sense similar to Varaiya-Lin strategies. Two cases of payoffs are considered: payoffs dependent on the whole trajectories and terminal payoffs.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka